Cavernous Lymphangioma of Unusual Location: A Case Report (Global Journal of Medical Research, 2019)
Lymphangioma is a benign tumor leading to hyperplasia of lymphatic vessels. The gold standard for treating lymphangiomas is surgical resection; alternative options being, sclerotherapy reduces the impact and complications of surgery.
Keywords: lymphangioma; cavernous lymphangioma; lymph